A importância do treino na transformação de um "Jogar" idealizado num "Jogar" realizado: Relatório de Estágio Profissionalizante realizado na equipa de sub-17 da Associação Académica de Coimbra / SF - Cláudio Filipe Simões Costa (2018)
This report was prepared based on professional stage realized in the under-17 team of Associação Académica de Coimbra / SF.The main purpose of this report is to describe and reflect about lived context and how was operated in functional context.In functional terms, the propose of professional stage was transform a game idea in a real idea through training operationalization.With this propose, the review of literature aims to guarantee the theoretical support through the understanding of fundamental concepts such as the Game Model, game conception, specificity, morfocycle, and the methodological principles that allowed the training operationalization.The characterization of Game Model, that is, the exposition of game conception, through interaction of principles in game moments, jointly with the contexts that emerged from the training have constituted as the principal focus of the report. The characterization and exposition with three weekly training session, simultaneously with the presentation of the evolutionary contexts of exercising in function of Morfocycle have composed operational process of Game Model)The conclusions that resulted of this operationalization are followers: the Game Model is a priority requirement in training development; the acquisition process of game idea depends on the correct articulation of principles in Morfocycle; the stability and evolution of Game Model depends of conditioning of exercise contexts that produce the specificity of Game Model.